The association between atopic disorders and keloids: A case-control study - Enes Hajdarbegovic; Annemieke Bloem; Deepak Balak; Bing Thio; Tamar Nijsten (Wolters Kluwer Medknow Publications, 2015)
Background: Keloids and atopic disorders share common inducing and maintaining inflammatory pathways that are characterized by T-helper cell 2 cytokines. Aims and Objectives: The objective of this study was to test for associations between keloids and atopic eczema, asthma and hay fever. Materials and Methods: This was a case-control study with 131 patients diagnosed with keloids at our dermatology outpatient clinic between 2000 and 2012. Controls were 258 partners of keloid or sarcoidosis patients. Patient who reported life time prevalences of atopic eczema, asthma and hay fever were assessed using a questionnaire based on The European Community Respiratory Health Survey (ECRHS) and The International Study of Asthma and Allergies in Children (ISAAC). Results: The prevalence of asthma was lower in keloid patients (19/131 vs. 20/258, P = 0.035), as was being diagnosed with asthma by a physician (18/131 vs. 19/258, P = 0.039) and using inhalators for asthma (13/131 vs. 7/258, P = 0.02). After adjusting for age and non-European descent the odds ratio for having a keloid was (adjusted OR = 4.44; 95% CI 1.59-12.40) in asthmatics using inhalators. There were no clear and consistent associations found for keloids with atopic eczema or with hay fever. Conclusion: In conclusion, our study shows that keloids may be strongly associated with atopic asthma. Atopic eczema and hay fever do not seem to be correlated with keloid. Further studies are warranted to assess the validity of atopic asthma as a risk factor for the development of keloid scars.